PENGARUH ENVIRONMENTAL SOCIAL GOVERNANCE (ESG), INTELLECTUAL CAPITAL, DAN SALES GROWTH TERHADAP KINERJA KEUANGAN - Deliyanti, Tria; Hadiwibowo, Imam; Azis, Mohammad Taufik (UNPERBA, 2025)
This research aims to examine the effect of Environmental Social Governance (ESG), Intellectual Capital (IC), and Sales Growth on the financial performance of non-financial companies listed on the IDX ESG Leaders in 2020-2023. The research method uses a quantitative approach with secondary data from annual financial reports and sustainability, and uses purposive sampling with a sample of 15 companies. Data analysis techniques include normality, multicollinearity, heteroscedasticity, and panel data regression tests with chow and hausman tests. The results showed that ESG has no significant effect on financial performance, while IC has a significant positive effect, and Sales Growth has no significant effect. The implication of this study is that companies need to focus on managing Intellectual Capital to improve financial performance, while ESG implementation and sales growth require a more mature strategy to have a positive impact on financial performance. This indicates that while ESG practices are important for long-term sustainability, and sales growth is an indicator of business expansion, their influence on financial performance can vary and is not always significant without proper management.